Evaluation of heating energy consumption patterns in the residential building sector using stepwise selection and multivariate analysis - Filippin, Maria Celina (2013)
The aim of the present study is to evaluate historical consumption of natural gas for heating, between 1996 and 2009, in multifamily buildings, using stepwise selection and multivariate analysis. 72 apartments of the capital of the province of La Pampa, Argentina, were studied. Some apartments were previously monitored, thus information about their thermal and energy behaviour is available. There are many variables that could influence the winter energy and annual consumption of the apartments. Based on the characteristics of buildings in Argentina and on previous research, ten variables were selected, from which the most representative ones were selected by using a stepwise method. Then, the apartments were grouped by applying clustering techniques, and the centroids for each cluster were determined by averaging the variables that describe the cluster. It was shown that the apartments monitored in previous works, having good thermal behaviour, are close to the centroids of the group to which they belong and could be taken as references of their group. The annual heating energy consumption average for the sample is 118.2 kWh/m2/y. However, a significant percentage of apartments showed energy consumptions lower than 70 kWh/m2/y, which is a widely accepted value to define a building as a "low-energy" one. Thus, some apartments could be classified as "low-energy", but for the actual Argentinean Norm they do not qualify even for the worst energy level label. The results make evident a strong disagreement between the Argentinean standard label and the real energy consumption for heating. This fact should be considered as fundamental in order to review the Norm.